NOVEL ANALYTICAL METHOD DEVELOPMENT AND VALIDATION FOR CEFOXITIN NEW β-LACTAM ANTIBIOTICS IN BULK AND DOSAGE FORM - Kumar, Amit (Journal of Biomedical and Pharmaceutical Research, 2019)
The Objective of this work based on for development of a novel method and validation of method used for determination of amount in manner of assay present into Cefoxitin in bulk and Tablet Dosage form. The aspire and intention of the present study is to expand moreover authenticate a novel as well as rapid reverse phase chromatography separation technique for the estimating Cefoxitin in bulk and dosage form to justify the presence of drug in the developed dosage forms and give satisfaction towards presence of medicine and its assay estimation. As the drug Cefoxitin compendial monograph is not available in Indian Pharmacopoeia and British Pharmacopoeia, but a compendial monograph is available in United Sate Pharmacopoeia i.e. USP- 40 for injection dosage form only. The developed method is new, simple, economic, rapid, eco friendly, accurate, and precise HPLC method for qualitative and quantitative estimation of Cefoxitin in bulk and dosage form like tablet, capsule, injection also.